2011
DOI: 10.1111/j.1469-8137.2011.03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the potential for triterpene synthesis in rice through genome mining and metabolic engineering

Abstract: Summary• The first committed step in sterol biosynthesis in plants involves the cyclization of 2,3-oxidosqualene by the oxidosqualene cyclase (OSC) enzyme cycloartenol synthase. 2,3-Oxidosqualene is also a precursor for triterpene synthesis. Antimicrobial triterpenes are common in dicots, but seldom found in monocots, with the notable exception of oat. Here, through genome mining and metabolic engineering, we investigate the potential for triterpene synthesis in rice.• The first two steps in the oat triterpene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 69 publications
2
38
0
Order By: Relevance
“…GC-MS has been combined with gene expression analysis to identify a number of genes involved in triterpene synthesis to also be present in rice. Expression of the oxidosqualene cyclase (OSC) enzyme AsbAB1 encoding the β-amyrin synthase in rice showed that rice is capable of β-amyrin synthesis [100] hence identifying the potential for metabolic engineering of saponin regulated resistance in other cereals. A method for the quantification of saponins using LC-MS/MS has recently been developed [101].…”
Section: Saponinsmentioning
confidence: 99%
“…GC-MS has been combined with gene expression analysis to identify a number of genes involved in triterpene synthesis to also be present in rice. Expression of the oxidosqualene cyclase (OSC) enzyme AsbAB1 encoding the β-amyrin synthase in rice showed that rice is capable of β-amyrin synthesis [100] hence identifying the potential for metabolic engineering of saponin regulated resistance in other cereals. A method for the quantification of saponins using LC-MS/MS has recently been developed [101].…”
Section: Saponinsmentioning
confidence: 99%
“…Interestingly, other monocotyledons such as rice and Brachypodium also contain CYP51H genes although these species are not known to accumulate saponins. Brachypodium has three CYP51H genes and two CYP51H pseudogenes, whereas rice has six CYP51Hs that are likely to be functional and three CYP51H pseudogenes [68], indicating that the CYP51Hs paralogues in these two monocotyledons are not stable. The oat CYP51H10 enzyme is the only example known so far of a CYP51 that has been duplicated and neofunctionalized to produce a specialized compound.…”
Section: Recruitment Of P450s For Triterpenoid Biosynthesismentioning
confidence: 99%
“…This is due partly to higher plants being complex multicellular organisms, in which terpene metabolism generally utilizes more complex innate machinery that can be compartmentalized intracellularly and to cell/tissue specificities (Lange and Ahkami, 2013;Kempinski et al, 2015). Significant efforts have been made to overcome these obstacles to improve the production of valuable terpenes in plants, including monoterpenes (Lücker et al, 2004;Ohara et al, 2010;Lange et al, 2011), sesquiterpenes (Aharoni et al, 2003;Kappers et al, 2005;Wu et al, 2006;Davidovich-Rikanati et al, 2008), diterpenes (Besumbes et al, 2004;Anterola et al, 2009), and triterpenes (Inagaki et al, 2011;Wu et al, 2012). Among these, engineering terpene metabolism into a subcellular organelle, where the engineered enzymes/ pathways can utilize unlimited/unregulated precursors as substrates, appears most successful.…”
mentioning
confidence: 99%